Genome-wide identification and comparative analysis of the AP2/ERF gene family in Prunus dulcis and Prunus tenella: expression of PdAP2/ERF genes under freezing stress during dormancy - Dongdong Zhang; Bin Zeng; Yawen He; Jiangui Li; Zhenfan Yu (BMC Genomics)
Abstract The AP2/ERF (APETALA2/ethylene responsive factor) transcription factor family, one of the largest in plants, plays a crucial role in regulating various biological processes, including plant growth and development, hormone signaling, and stress response. This study identified 114 and 116 AP2/ERF genes in the genomes of 'Wanfeng' almond (Prunus dulcis) and 'Yumin' wild dwarf almond (Prunus tenella), respectively. These genes were categorized into five subfamilies: AP2, DREB, ERF, RAV, and Soloist. The PdAP2/ERF and PtAP2/ERF members both demonstrated high conservation in protein motifs and gene structures. Members of both families were unevenly distributed across eight chromosomes, with 30 and 27 pairs of segmental duplications and 15 and 18 pairs of tandem repeated genes, respectively. The promoter regions of PdAP2/ERF and PtAP2/ERF family members contained numerous important cis-elements related to growth and development, hormone regulation, and stress response. Expression pattern analysis revealed that PdAP2/ERF family members exhibited responsive characteristics under freezing stress at different temperatures in perennial dormant branches. Quantitative fluorescence analysis indicated that PdAP2/ERF genes might be more intensely expressed in the phloem of perennial dormant branches of almond, with the opposite trend observed in the xylem. This study compared the characteristics of PdAP2/ERF and PtAP2/ERF gene family members and initially explored the expression patterns of PdAP2/ERF genes in the phloem and xylem of perennial dormant branches. The findings provide a theoretical foundation for future research on almond improvement and breeding, as well as the molecular mechanisms underlying resistance to freezing stress.